Comparation of Production and Financial Analysis of Broiler Farm with Close House and Open House Farm System in Partnership Patterns - Adib Norma Respati; Abdul Hakim; Andri Haryono Awalokta Kusuma (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
This research aimed to determine the comparation of production and financial analysis of broiler farm with close house and open house farm system in partnership patterns. This research was conducted on August 2019 in Surakarta. The variable measured were feed intake, average of final body wieght, average slaughter age, depletion, Feed Convertion Ratio (FCR), Performance Index (PI), Average daily gain (ADG), R/C Ratio and income. Data were analysed descriptively. The result shows the difference between broiler farm with close house and open house farm system in partnership patterns. The result showed that feed intake, PI, ADG, R/C Ratio of broiler farm with open house system were higher than that of close house system. Farmer income per production with open house system is higher (Rp. 4,334) than that of close house system (Rp. 4,001). In conclusion, broiler farm with open house system in partnership patterns is more beneficial than close house system. Key words : broiler, closed house, income, open house.